2014
DOI: 10.1088/1674-4926/35/2/024011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of defect states on the performance of CuInGaSe2solar cells

Abstract: Device modeling has been carried out to investigate the effects of defect states on the performance of ideal CuInGaSe 2 (CIGS) thin film solar cells theoretically. The varieties of defect states (location in the band gap and densities) in absorption layer CIGS and in buffer layer CdS were examined. The performance parameters: open-circuit voltage, short-circuit current, fill factor, and photoelectric conversion efficiency for different defect states were quantitatively analyzed. We found that defect states alw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The most efficient cell is the one where the SDL is modeled (CIGS/SDL/ZnS/ZnO). This is in good agreement with the work of Wan et al in 2014 [ 22 ] and Ouédraogo et al in 2014, [ 12 ] who showed that the modeling of the SDL would make it possible to get closer to the real model of a cell structure. It is also in line with Touafek et al [ 13 ] statement who advocated that the formation of a SDL play a major role in the suppression of interface recombination, enabling improving the performance.…”
Section: Resultssupporting
confidence: 91%
“…The most efficient cell is the one where the SDL is modeled (CIGS/SDL/ZnS/ZnO). This is in good agreement with the work of Wan et al in 2014 [ 22 ] and Ouédraogo et al in 2014, [ 12 ] who showed that the modeling of the SDL would make it possible to get closer to the real model of a cell structure. It is also in line with Touafek et al [ 13 ] statement who advocated that the formation of a SDL play a major role in the suppression of interface recombination, enabling improving the performance.…”
Section: Resultssupporting
confidence: 91%
“…However, when the defect density increases more than 10 17 cm −3 , V OC increases from 0.85 V and reaches 1.05 V for the defect density of 10 19 cm −3 . The alteration in V OC for the defect density of 10 19 cm −3 , can be attributed to the built-in electric field of the p–n junction which has the opposite direction compared with the normal p–n junction [ 10 , 39 ]. The current density J SC shows a steady level until the defect density goes beyond 10 17 cm −3 and then, it sharply reduces to 2.91 mA/cm 2 from 28.40 mA/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…As buffer layer thickness increases, the amounts of photons absorbed outside the hole diffusion length region increase which may lower the recombination rate [ 37 ]. There is not much effect of TCO SnO 2 layer thickness, thus it has been kept at a minimum value to achieve low series resistance [ 38 , 39 ]. The optimized thicknesses can be found in Table 1 .…”
Section: Structures and Methodologymentioning
confidence: 99%